Bermazhab adalah Keniscayaan Sejarah - Khoerul Umam (Jurnal Syariah dan Hukum Komparatif, 2022)
At the time of the Prophet Muhammad SAW, Islamic law was never different because the Prophet Muhammad was the only human being who had the authority and legality to convey Islamic law through the al-Quran and Hadis. The understanding of the companions at the time of the Prophet Muhammad SAW had the same legal perspective on each of the same problems and if they found a new problem they only asked for the law from the Prophet Muhammad. After the Prophet Muhammad’s death, differences of opinion began to occur among the Muslims. This happened because the Prophet Muhammad himself had said to do ijtihad if he did not find the law in the al-Quran and Hadis. Therefore, the companions had their own ijtihad in solving the problems they faced. In the next era, differences of opinion continued to occur, even the implications of these differences formed a mazhab that still exists today. The Muslim community cannot be separated from the mazhab because in making Islamic law or the method of making Islamic law, they must use the work of the scholars of the mazhab.